Pengelolaan Peserta Didik dalam Upaya Meningkatkan Motivasi Belajar di Masa Pandemi - Ega Regiani; Isna Nadifah Nur Fauziah; Selly Ade Saputri (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of student management, especially classroom management in an effort to increase students' learning motivation during the pandemic. During this pandemic, various aspects of human life have undergone many changes, especially in the education aspect. This research uses qualitative research methods and literature review. In collecting the data itself, this study uses a literature study, with data coming from various sources of observational literature studies, such as articles, journals, or books related to the influence of student management in an effort to increase students' learning motivation. Learning during the Covid-19 pandemic uses an online system which causes several problems, one of which is the decline in students' learning motivation. The problem of decreasing learning motivation requires a solution, one of which is good student management. Student management has a major influence on student learning motivation during this pandemic. By managing the class well, it will have a positive influence on students' learning motivation during the covid-19 pandemic, activities that can be carried out such as holding an integrated Distance Learning Program. With this paper, it is hoped that it can be a reference for educators and those who have relationships with the world of education in making good classroom management a solution to increase the potential of existing classes and make classes more interactive so that students' learning motivation increases.